2009
DOI: 10.1016/j.breast.2009.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Improving the therapeutic index of anthracycline chemotherapy: Focus on liposomal doxorubicin (Myocet™)

Abstract: Anthracyclines are valuable cytotoxic agents in cancer treatment. However, their usefulness is limited by cumulative dose-dependent cardiotoxicity that may manifest as life-threatening congestive heart failure. To avoid cardiotoxicity, the use of doxorubicin is typically capped at a safe cumulative dose. Liposomal formulations may reduce cardiac risks whilst maintaining anti-cancer efficacy. Efficacy and safety studies of non-pegylated liposomal doxorubicin (NPLD) in metastatic breast cancer (MBC) are reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
115
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(117 citation statements)
references
References 51 publications
1
115
1
Order By: Relevance
“…Apart from destroying adjacent normal cells (11), these treatments also cause severe side effects (12)(13)(14). Therefore, current studies have focused on the search for alternative medicines from plant-based sources.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from destroying adjacent normal cells (11), these treatments also cause severe side effects (12)(13)(14). Therefore, current studies have focused on the search for alternative medicines from plant-based sources.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, we further demonstrated that the combination of liposomal M-V-05 with a pegylated liposome formulation of doxorubicin would yield additive cancer cell killing effect, with the potential of reducing the dose of liposomal doxorubicin needed for the same biological effect. As the pegylated liposome doxorubicin could give rise to palmar-plantar erythrodysesthesia (or hand-foot syndrome) with an overall incidence of 48% in MBC patients (24), it is thus beneficial to be able to reduce the dose of liposomal doxorubicin through the combinatorial use with liposomal M-V-05. In conclusion, liposomal M-V-05 is an effective therapy for breast cancer, and could be a novel adjuvant to liposomal doxorubicin therapy.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] The US Food and Drug Administration has approved for cancer therapy the use of doxorubicin encapsulated in liposomes (Doxil) and paclitaxel attached to nanoparticles (Abraxane). 8,9 In cancer chemotherapy, the clinician aims to achieve a good therapeutic index, which is the ratio of the lethal dose for 50% of the population to the minimum effective dose for 50% of the population. 10 But cancer is most often…”
Section: Introductionmentioning
confidence: 99%